Peroxide value and DPPH (diphenyl picril hydrazil hydrate) free radical scavenger activity of Knema laurina methanol extract - ., Praptiwi; Dewi, Puspa; Harapini, Mindarti (Faculty of Pharmacy Universitas Gadjah Mada, Yogyakarta, Skip Utara, 55281, Indonesia, 2006)
The aim of the study were to determine the peroxide value and anti DPPH free radical scavenger activity of Knema laurina (Myristicaceae) methanol extract as indicator og antioxidant properties. Peroxide value wasdetermined by iodometri-titration method while anti DPPH free radical was determined by spectrophotometry. Based on phytochemical screening, the chemical compounds of K. laurina were essential oil, sterol, triterpen, tannin, peroxide sugar, alkaloid and saponin. Peroxide value (POV) of K. laurina methanol extract was 158.07 peroxide/1kg sample, while POV of Î±- tocopherol was 363.96 peroxide/1kg sample. It mean that the inhibition of oxidation process of K. laurina methanol extract was better that that of Î±-tocopherol so the peroxide formed was lower. The IC50 of K. laurina methanol extract was 39.72 ppm, while IC50 of vitamin C was 12.20 ppm. The result showed that methanol extract of K. laurina at the concentration of 39.72 ppm inhibit 50% of free radical DPPH activity. Based on the peroxide value and IC50 of K. laurina methanol extract, it can be concluded that K. laurina methanol extract had potential activity as anti-DPPH free radical and could be acted as reductor in oxidation process.Key words : Knema laurina, peroxide value (POV), free radical DPPH